KONSEP PELAYANAN DALAM PENINGKATAN KUALITAS PENDIDIKAN DI SEKOLAH - Sulaeha, Sulaeha (Paedagogia: Jurnal Pendidikan, 2017)
Implementation of the decentralization of education requires principals and school supervisors to develop an effective and productive, with full independence and accountability. Education Indonesian nation today is very alarming many cases that occur in every country. The problem of education in Indonesia is increasingly complicated, multiply and complex. One of the educational problems faced by the people of Indonesia are the low quality/quality of education at all levels and educational unit, although it may have been many efforts made to improve the quality of national education, such as curriculum, national and local, improving the competence of teachers through the provision of books and learning tool as well certification programs, procurement and improved infrastructure and improving the quality of school management. Nevertheless, various indicators of the quality of education have not shown significant improvement. Some schools, especially in Palu showed an increase in the quality of education is quite encouraging, but others are still apprehensive.